1966
DOI: 10.1084/jem.123.1.161
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopic Observations on Antibody-Producing Lymph Node Cells

Abstract: The direct demonstration by McMaster and Hudack (1) of the production of antibody in lymph nodes led to a long search for the cell in the lymph node which synthesized antibody. Early evidence by Harris, Grimm, Mertens, and Ehrich (2), Dougherty, Chase, and White (3), and Harris and Harris (4) that the lymphocyte was the cell of synthesis was followed by the studies of BjSrnehoe and Gormsen (5), and Fagraeus (6) indicating the plasma cell as the cell which produced antibody. The following years produced studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
37
1
7

Year Published

1966
1966
1980
1980

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 120 publications
(52 citation statements)
references
References 27 publications
7
37
1
7
Order By: Relevance
“…In confirmation of previous studies from this and other laboratories, it was shown that lymphocytes and plasmacytes in various stages of differentiation contributed to the heterogeneity of the antibody-producing cells (2)(3)(4)(5)(6)(7)(8). Morphological forms suggesting transition between cells of the lymphocytic and of the plasmacytic series were also described (1).…”
supporting
confidence: 71%
“…In confirmation of previous studies from this and other laboratories, it was shown that lymphocytes and plasmacytes in various stages of differentiation contributed to the heterogeneity of the antibody-producing cells (2)(3)(4)(5)(6)(7)(8). Morphological forms suggesting transition between cells of the lymphocytic and of the plasmacytic series were also described (1).…”
supporting
confidence: 71%
“…These cells, therefore, do not resemble typical secretory ceils. Nevertheless, it is well recognized that small lymphocytes can secrete antibodies (25). The present studies indicate that a population from normal spleen consisting of virtually all small lymphocytes incorporates tyrosine-3H into 7S IgG and 8S IgM molecules which are actively secreted.…”
Section: Discussionmentioning
confidence: 79%
“…Braunsteiner and Pakesch (14) were able to show increases in plasma cells in the blood of rabbits after repeated injections of typhoid vaccine. Hummeler et al (16) and Harris et al (25) described the electron microscopic appearance of the lymphoid cells which were synthesizing antibody. Their studies included lymph node material, lymph, and peripheral blood after immunization of rabbits with sheep red cells.…”
Section: Study Of Patients During Bacterial and Viralmentioning
confidence: 99%